ROLE MODEL AND ENTREPRENEURIAL PERFORMANCE: THE ROLE OF ENTREPRENEURIAL IDENTITY AND SELF-EFFICACY AS INTERVENING VARIABLE - Efrata, Tommy Christian; Maichal, Maichal (Universitas Brawijaya, Indonesia, 2018)
This study aims to assess how the role of entrepreneurial identity and selfefficacy in mediating the relationship between the role model and entrepreneurial performance. The population selected in this study is students of UniversitasCiputra who have been running start-up business for 2 to 3 years, with the turnover of fewer than 4.8 billion per year. The results of this research indicate a pattern that connects the existence of a role model and entrepreneurial performance, where the influence is mediated by entrepreneurial identity and self-efficacy. The existence of a role model is proven to influence the formation of entrepreneurial identity. The more individuals perceive themselves as an entrepreneur, the higher their confidence in their ability in setting up and running a business. The high level of confidence in their ability that they will be successful will have a direct impact on the improvement in entrepreneurial performance.